The effect of heat treatment on fatigue and mechanical properties of 6061 aluminium alloy - Nasir, Nurulhilmi Zaiedah; Mohd Daud, Mohd Ahadlin; Selamat, Mohd Zulkefli; Rivai, Ahmad; Dhar Malingam, Sivakumar (Trans Tech Publications Ltd., 2015)
This paper investigated the effect of heat treatment on mechanical properties and microstructure of 6061 aluminium alloy. The aluminium alloys were examined in the heat treated conditions, using different quenching media, water and oil. The alloy was solution heat treated at temperature of 529oC for one, three and five hour respectively. Aging treatment was carried out at temperature of 160oC which is assumed to be the best temperature for ageing process. Hardness measurement was carried out using a Brinell Hardness Tester Machine. The results shows hardness and impact strength are inversely proportional to each other, as the hardness of 6061 aluminium alloy decreases and impact strength increases.